Measuring attitudes to Income Risk:Evidence from the Cypriot Society - PAFITOU, MARINA MP (2012)
This dissertation was designed to elicit differences in risk aversion across demographic groups based on gender, age, education level, marital status or income, with particular reference to the context of income risk. It is probably the first empirical study in Cyprus, aiming to examine individuals’ attitudes towards income risk. In order to examine the hypothesized relationships of this dissertation, three different statistical approaches were utilized, which is a very interesting aspect of this dissertation since results of these different approaches could be compared and analysed. No statistically significant relationship between gender and relative risk aversion was found in any of the three different approaches used. Also, no statistically significant relationship was found between education level and relative risk aversion in any of the three approaches. The results about age differ across the three approaches since a significant relationship was found only under the third approach. This is also the case for marital status since a significant relationship was found under the first and second approaches. As concerns income, a statistically significant relationship was found under the second and third approaches.